RANCANG BANGUN SISTEM KONTROL PERAWATAN IKAN KOI BERBASIS IOT (INTERNET OF THINGS) - Fais Aqorni; Resti Amalia (CV. Multi Kreasi Media, 2024)
The design of an IoT-based Control System for Koi Fish Care is a monitoring system that provides automatic temperature and feeding control for Koi fish in an aquarium. This system uses the DS18B20 Temperature Sensor and the HC-SR04 Ultrasonic Sensor as inputs to detect the temperature and distance of the fish in the aquarium. The NodeMCU is used as a data processor, and the Motor Servo and fan are used as outputs to regulate the ideal temperature and distance. A Real-Time Clock (RTC) is also utilized for the automatic feeding time. The Motor Servo serves as the output to drive the feeder. This prototype can be stored in the aquarium to monitor temperature and distance using a smartphone device.